The chain mediating effects of resilience and perceived social support in the relationship between perceived stress and depression in patients with COVID-19 - Wang, Lingling; Yu, Jing; Diao, Xuqian; Zhang, Yuanbei; Miao, Ye; He, Wei (Frontiers in Psychology, 2024)
Introduction Perceived stress and depression were indirect effects of the COVID-19 pandemic, especially in square-cabin hospitals. It was paramount to understand their mediating effects, which might detonate factors that led to mental illness. Materials and methods We conducted a cross-sectional study to investigate perceived stress and depressive symptoms among patients with COVID-19 in Shanghai square-cabin hospitals from April 18 to May 19, 2022. The questionnaire included the Perceived Stress Scale 10, Patient Health Questionnaire 9, Perceived Social Support Scale, and the Connor-Davidson Resilience Scale 10. Results This study investigated the chain-mediating roles of perceived social support and resilience in the relationship between perceived stress and depression. Perceived stress positively predicted depression (r = 0.613, p < 0.01), negatively correlated with perceived social support (r = −0.318, p < 0.01) and resilience (r = −0.398, p < 0.01). In the chain mediating model, perceived stress had significant direct predictive effects on depression, and significant indirect predictive effects on depression through perceived social support and/or resilience. Conclusion It showed that higher perceived social support and resilience were associated with lower perceived stress among COVID-19 patients, which might lead to symptoms of mild depression, and highlights the importance of resilience and perceived social support in reducing depressive symptoms.